Соціально-психологічні чинники забезпечення психологічного благополуччя молодших школярів в освітньому середовищі. - Собкова, Світлана (Центр професійного розвитку PsyUpgrade, 2025)
This article addresses the pressing issue of ensuring the psychological well-being and safety of junior schoolchildren as a strategic goal of the modern Ukrainian educational system. A thorough theoretical analysis of scholarly approaches to defining the educational environment and psychological safety has been conducted. It is substantiated that the teacher's style of educational influence is a key socio-psychological factor that directly determines the level of student comfort, impacting the formation of the child's locus of control and self-efficacy. The results of an empirical study conducted on a representative sample of primary school students and teachers are presented. Using methods of mathematical and statistical processing, it was established that a strong positive correlation exists between a democratic interaction style and high indicators of self-confidence. The study revealed that in classes where an authoritarian style dominates, a significant portion of students demonstrates a low level of confidence, which is statistically confirmed by a strong inverse relationship between these indicators, as well as a direct link to an increased level of anxiety. An extended analysis indicates the systemic nature of the style's influence on the children's psychological state. The conclusion is made about the necessity of forming a psychologically safe and democratic environment as a mandatory condition for the implementation of modern educational requirements.
-
Keywords: психологічний комфорт; освітнє середовище; психологічна безпека; молодший шкільний вік; стиль виховного впливу; математико-статистичне опрацювання; кореляційний аналіз.